ESTIMATION OF ROTATION PARAMETERS OF THREE-DIMENSIONAL IMAGES BY SPHERICAL HARMONICS ANALYSIS - Rozhentsov, Alexey; Egoshina, Irina; Baev, Alexey; Chernishov, Daniil (Journal of Applied Engineering Science, 2018)
The article describes a method for estimating the rotational parameters of three-dimensional objects defined as a cloud of points in three-dimensional space, which is less complex compared to other methods and it can ensure a single-valued solution. The authors propose an approach of vector-field models to parametrize images of complex three-dimensional objects. The paper discusses the ways for calculating the expansion coefficients in the basis of spherical harmonics for images of three-dimensional point cloud objects. The authors offer an approach that provides the possibility of estimating the rotation parameters of three-dimensional objects from the values of the expansion coefficients in the basis of spherical harmonics.
Keywords: spherical harmonics; estimation of parameters; point cloud; rotation of three-dimensional objects